Efficacy of clonidine as an additive to levobupivacaine for epidural anesthesia and post-operative analgesia in infraumbilical surgeries – A randomized and double blind study - Arunkumar Arumugam; Bharti Badlani; Singh, Puja; Tripathi, Sonali (Asian Journal of Medical Sciences, 2022)
Background: Epidural anesthesia as a safe alternative to general anesthesia is commonly used for inducing anesthesia and post-operative analgesia in patients undergoing infraumbilical surgeries. The addition of an adjuvant not only increases the effectiveness of a local anesthetic by prolonging and intensifying the sensory blockade but also causes reduction in the dose of rescue analgesic agent in post-operative period. Clonidine is a potent and selective α-2-adrenoceptor agonist with analgesic potency. Aims and Objectives: This study was conducted to evaluate the efficacy of clonidine as an additive to levobupivacaine in infraumbilical surgeries. Materials and Methods: One hundred patients of American Society of Anesthesiologists Grade I or II who were undergoing infraumbilical surgery were randomly divided into two groups as levobupivacaine (L) and levobupivacaine with clonidine (LC). Patients were allocated to one of the two groups by computer generated random selection. Group L received 0.5% levobupivacaine (1.5 mg/kg) and Group LC received 0.5% levobupivacaine (1.5 mg/kg) with clonidine (2 μg/kg). The onset time for sensory, motor blockade, duration of anesthesia and duration of analgesia, and Visual Analog Scale (VAS) score were observed in both the groups. The hemodynamic variables such as heart rate, systolic and diastolic blood pressure, respiratory rate, and oxygen saturation at various time intervals were measured. Any untoward side effects were noted in both groups. Results: The onset of sensory (7.8±1.7 min) and motor blockade (10.9±1.9 min) were significantly faster in clonidine group. Duration of anesthesia and duration of analgesia were prolonged in Group LC (234.5±16.1 min, 412.8±48.3 min) compared to Group L (173.56±12.78 min, 269.2±24.2 min) which was statistically significant (P<0.05). Similarly, clonidine group had less VAS score compared to control group. There was no significant change in the hemodynamic variables between the two groups. Hypotension and bradycardia were found more in clonidine group compared to the control group. Conclusion: Clonidine as an adjuvant to levobupivacaine prolongs the post-operative analgesia and the duration of anesthesia for infraumbilical surgeries.